Alternative castor oil-based polyurethane adhesive used in the production of plywood - Dias,Fabricio Moura (2004)
Plywood is normally produced with urea-formaldehyde and/or phenol-formaldehyde adhesives. However, the former is considerably toxic and environmentally damaging, while the latter is expensive, thus motivating the search for alternative raw materials in plywood production. The castor oil-based polyurethane adhesive developed at the São Carlos Institute of Chemistry, University of São Paulo, is an environmentally friendly vegetal oil-based polymer that is harmless to humans. The wood species Eucalyptus grandis offers favorable properties for plywood the manufacture. The study reported on here involved the use of castor oil-based polyurethane adhesive to produce plywood with Eucalyptus grandis layers. The plywood's performance was evaluated based on the results of physical and mechanical tests recommended by the Brazilian code, ABNT. Tests results showed higher values than those reported in the literature and recommended by the ABNT, indicating that the castor oil-based polyurethane adhesive is a promising glue for the manufacture of plywood.